2017
DOI: 10.3390/nu9091037
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin Supplementation Improved Risk Factors of Coronary Heart Disease in Individuals with Low HDL-C Levels

Abstract: Low high-density lipoprotein cholesterol (HDL-C) is associated with an increased risk of coronary heart disease (CHD). This study aimed to evaluate the effects of capsaicin intervention on the serum lipid profile in adults with low HDL-C. In a randomized, double-blind, controlled clinical trial, 42 eligible subjects were randomly assigned to the capsaicin (n = 21, 4 mg of capsaicin daily) or to the control group (n = 21, 0.05 mg of capsaicin daily) and consumed two capsaicin or control capsules, which containe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 39 publications
1
35
0
1
Order By: Relevance
“…After removing 35 duplicates, 401 papers remained, which were manually screened on title and abstract for inclusion criteria. Full texts of 39 articles were obtained and reviewed, which resulted in the selection of 11 studies that were found eligible for qualitative synthesis (Ahuja and Ball 2006;Inoue et al 2007;Kim et al 2010;Kang et al 2016;Yuan et al 2016;Hochkogler et al 2017;Lee et al 2017;Qin et al 2017;Taghizadeh et al 2017;Urbina et al 2017;Arent et al 2018). Manual search of the reference lists of the eligible articles lead to the identification of three additional studies (Snitker et al 2009;Cha et al 2013;Lim et al 2015), thereby increasing the total number of eligible studies to 14.…”
Section: Search Resultsmentioning
confidence: 99%
“…After removing 35 duplicates, 401 papers remained, which were manually screened on title and abstract for inclusion criteria. Full texts of 39 articles were obtained and reviewed, which resulted in the selection of 11 studies that were found eligible for qualitative synthesis (Ahuja and Ball 2006;Inoue et al 2007;Kim et al 2010;Kang et al 2016;Yuan et al 2016;Hochkogler et al 2017;Lee et al 2017;Qin et al 2017;Taghizadeh et al 2017;Urbina et al 2017;Arent et al 2018). Manual search of the reference lists of the eligible articles lead to the identification of three additional studies (Snitker et al 2009;Cha et al 2013;Lim et al 2015), thereby increasing the total number of eligible studies to 14.…”
Section: Search Resultsmentioning
confidence: 99%
“…In addition, other lipids like apolipoproteins, glucose levels, and other parameters did not significantly change in the human body cycle. In conclusion, capsaicin improved risk factors of CHD in individuals with low HDL-cholesterol and may contribute to the prevention and treatment of CHD [25].…”
Section: Capsaicin and Heart Diseasementioning
confidence: 88%
“…Moreover, the benefits of capsaicin on obesity, diabetes, CVD, various cancers, and dermatologic problems have been reported [ 39 , 40 , 41 ]. Intake of 4 mg of capsaicin daily significantly improved HDL levels and reduced triglyceride and C-reactive protein levels in healthy human [ 42 ].…”
Section: Spices With Potential Atheroprotective Effectsmentioning
confidence: 99%
“…Although saffron, turmeric, and chili pepper had neutral effects on blood pressure, cinnamon demonstrated significant blood pressure lowering effects in patients with diabetes. Moreover, garlic has been shown to have the potential to reduce blood pressure in hypertensive patients [ 29 , 42 , 49 , 107 , 108 ]. These studies provide information on the beneficial roles of spices in reducing cardiovascular risk factors.…”
Section: Recommendations For Diet Adjustment In Prevention Of Cvdmentioning
confidence: 99%